ANALYSIS OF THE SOCIO-ECONOMIC EFFECT AND PERFORMANCE EXPECTANCY ON THE USE OF FINANCIAL TECHNOLOGY APPLICATIONS - Kussujaniyatun S.; Sujatmika; Harilaksana D.; Hartati A.S. (Russian Journal of Agricultural and Socio-Economic Sciences, 2022)
This study aims to analyze the socio-economic dimensions and performance expected by customers in using Kredit Adil Cooperative application fintech, Sakti.link. This research was carried out at the Kredit Adil Cooperative in Dlingo, Bantul, the only cooperative that has used fintech and serves areas spread across Bantul. Data was collected by survey method on 200 respondents with purposive sampling technique. The data analysis technique used Structural Equation Modeling (SEM) PLS. The results show that the socio-economic effect that affect customers using fintech in cooperatives are income, occupation, the distance (space) of the customer's domicile with financial institutions, and education (education). The variable of performance expectancy that affect the use of fintech include cost efficiency, residual income, ability to disburse loans/liquidity (ability to disburse loans), time efficiency (time efficiency), and environmentally friendly (paperless). The use of fintech is seen based on transaction traffic, the number of users, and changes in the structure of outstanding loans and bad loans.